The evolution, morphology, and development of fern leaves - Vasco, Alejandra; Moran, Robbin C.; Ambrose, Barbara A. (Frontiers in Plant Science, 2013)
Leaves are lateral determinate structures formed in a predictable sequence (phyllotaxy) on the flanks of an indeterminate shoot apical meristem. The origin and evolution of leaves in vascular plants has been widely debated. Being the main conspicuous organ of nearl all vascular plants and often easy to recognize as such, it seems surprising that leaves have had multiple origins. For decades, morphologists, anatomists, paleobotanists, and systematists have contributed data to this debate. More recently, molecular genetic studies have provided insight into leaf evolution and development mainly within angiosperms and, to a lesser extent, lycophytes. There has been recent interest in extending leaf evolutionary developmental studies to other species and lineages, particularly in lycophytes and ferns. Therefore, a review of fern leaf morphology, evolution and development is timely. Here we discuss the theories of leaf evolution in ferns, morphology and diversity of fern leaves, and experimental results of fern leaf development. We summarize what is known about the molecular genetics of fern leaf development and what future studies might tell us about the evolution of fern leaf development.